2011
DOI: 10.1590/s0102-311x2011001200009
|View full text |Cite
|
Sign up to set email alerts
|

Óbito por dengue como evento sentinela para avaliação da qualidade da assistência: estudo de caso em dois municípios da Região Nordeste, Brasil, 2008

Abstract: Despite the existing resources for adequate dengue patient care in the Brazilian healthcare system, the case-fatality rate for the disease is still high in the country. In order to identify factors associated with dengue-related death, this study evaluated quality of care according to the degree of implementation of specific measures, the technical and scientific quality of care, and access to health services in two municipalities (counties) in Northeast Brazil. An evaluative study of the implementation analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 19 publications
1
30
0
13
Order By: Relevance
“…Additionally, 5 patients had no access to an ICU bed, and 2 arrived at the hospital with advanced disease. Similar findings were observed in a descriptive study on 14 deaths due to dengue in 2 municipalities in northeastern Brazil (30). The durations of fever and hospital stay were shorter in cases than in controls, suggesting that the clinical condition of the cases on admission was worse than that of the controls, which may have contributed to the worse outcomes observed for the cases.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, 5 patients had no access to an ICU bed, and 2 arrived at the hospital with advanced disease. Similar findings were observed in a descriptive study on 14 deaths due to dengue in 2 municipalities in northeastern Brazil (30). The durations of fever and hospital stay were shorter in cases than in controls, suggesting that the clinical condition of the cases on admission was worse than that of the controls, which may have contributed to the worse outcomes observed for the cases.…”
Section: Discussionsupporting
confidence: 89%
“…The authors concluded that the occurrence of death was directly related to the clinical management of the cases, that patient care has not reached the level expected in any of the evaluated services, and that the recommendations from the Ministry of Health for the management of dengue cases are not being followed. According to the authors, the warning signs of dengue and those of shock due to the disease are not routinely investigated, and professionals have not used the clinical classification as recommended by the Ministry of Health [21]. …”
Section: Discussionmentioning
confidence: 99%
“…These social inequalities may lead to several disadvantages, ranging from a lack of health promotion to a reduced capability to successfully treat severe and potentially fatal cases, resulting from limited access to early diagnosis and timely clinical management 23,24 .…”
Section: Discussionmentioning
confidence: 99%